2020
DOI: 10.1038/s41536-020-0089-0
|View full text |Cite
|
Sign up to set email alerts
|

A subset of SMN complex members have a specific role in tissue regeneration via ERBB pathway-mediated proliferation

Abstract: Spinal muscular atrophy (SMA) is the most common genetic disease in children. SMA is generally caused by mutations in the gene SMN1. The survival of motor neurons (SMN) complex consists of SMN1, Gemins (2-8), and Strap/Unrip. We previously demonstrated smn1 and gemin5 inhibited tissue regeneration in zebrafish. Here we investigated each individual SMN complex member and identified gemin3 as another regeneration-essential gene. These three genes are likely pan-regenerative, since they affect the regeneration of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The protein was initially reported as the RNA-binding protein (RBP) of the survival of motor neurons (SMN) complex [ 2 ]. More recently, the protein has been implicated in translation control, and gene expression reprogramming [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The protein was initially reported as the RNA-binding protein (RBP) of the survival of motor neurons (SMN) complex [ 2 ]. More recently, the protein has been implicated in translation control, and gene expression reprogramming [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among others, Gemin5 has been identified as a signal recognition particle (SRP)-interacting protein [63], as a ribosome-interacting factor [64,65], as a translation regulator of several mRNAs [66][67][68][69], or as a factor involved in trans-splicing [70]. Further supporting the involvement of this multifaceted protein in different activities, recent data have shown that Gemin5 can act as a reprogramming factor in zebrafish lateral line hair cells, allowing for a shift toward cell survival [71]. In addition, an RNA-Seq analysis revealed that the gemin5, together with smn1 and gemin3 genes, are linked to a common set of genetic pathways, including the tumor protein tp53 and the epidermal growth factor receptor ErbB pathways.…”
Section: The Modular Structure Of Gemin5: Implications For Its Multifmentioning
confidence: 98%
“…In recent years, Gemin5 has emerged as a critical factor during translational reprogramming events, although the mechanisms underlying this phenomenon are still poorly known [71]. In this respect, previous studies have shown that Gemin5 regulates translation through its capacity to recognize a selective subset of mRNAs [68] and also serves as a hub for numerous RBPs [64] that, in turn, are involved in gene expression control.…”
Section: Promoting and Repressing Roles Of Gemin5 In Translation Controlmentioning
confidence: 99%
“…Accordingly, Gemin5 acts as a hub for several networks performing diverse key cellular functions. This multifunctional protein has been shown to act as a regulator of translation ( Pacheco et al, 2009 ; Workman et al, 2015 ; Francisco-Velilla et al, 2018 ), as a ribosome-interacting protein ( Francisco-Velilla et al, 2016 ; Simsek et al, 2017 ), as a reprogramming factor in zebrafish lateral line hair cells ( Pei et al, 2020 ), as a signal recognition particle-interacting protein ( Piazzon et al, 2013 ), and as a trans-splicing factor ( Philippe et al, 2017 ). In addition, Gemin5 has been identified as a member of RNP networks associated to distinct cytoplasmic aggregates ( Jiang et al, 2018 ; Vu et al, 2021 ; Wollen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%